Genomic and Proteomic Characterization of Bacteriocin-Producing Leuconostoc mesenteroides Strains Isolated from Raw Camel Milk in Two Southwest Algerian Arid Zones. (7th April 2014) - Benmechernene, Zineb; Fernández-No, Inmaculada; Quintela-Baluja, Marcos; Böhme, Karola; Kihal, Mebrouk; Calo-Mata, Pilar; Barros-Velázquez, Jorge
Abstract : Information on the microbiology of camel milk is very limited. In this work, the genetic characterization and proteomic identification of 13 putative producing bacteriocin Leuconostoc strains exhibiting antilisterial activity and isolated from camel milk were performed. DNA sequencing of the 13 selected strains revealed high homology among the 16S rRNA genes for all strains. In addition, 99% homology with Leuconostoc mesenteroides was observed when these sequences were analysed by the BLAST tool against other sequences from reference strains deposited in the Genbank. Furthermore, the isolates were characterized by matrix-assisted laser desorption/ionization time of flight mass spectrometry (MALDITOF MS) which allowed for the identification of 2 mass peaks 6242 m/z and 5118 m/z that resulted to be specific to the species L. mesenteroides . Remarkably, the phyloproteomic tree provided more intraspecific information of L. mesenteroides than phylogenetic analysis. Accordingly, phyloproteomic analysis grouped L. mesenteroides strains into different subbranches, while all L. mesenteroides isolates were grouped in the same branch according to phylogenetic analysis. This study represents, to our knowledge, the first report on the use of MALDI-TOF MS on the identification of LAB isolated from camel milk.